Strategic Alliance in Energy Sector & Implications for Economic Growth and Technical Efficiency: The Case of Petrobras and Galp - De Avila Arroyo, Jomar Patricia; Yago, Milton; Nasir, Muhammad Ali; Wu, Junjie (International Journal of Energy Economics and Policy, 2014)
This study stemmed from the lack of evidence and uncertainties regarding the economic and political effects of a strategic alliance between leading oil companies like Petrobras and Galp on their host economies. This paper investigates whether public and private corporations in the energy sector can influence the economic growth of their respective countries. A Panel data analysis was performed by employing quarterly data from (2006-2013). We also used Data Envelopment Analysis (DEA) approach to measure the technical efficiency (TE) effect of the alliance on the performance of both companies from 1999 to 2012. It was found the exploration and export of oil and gas do not play a significant role in output growth of the home economy and that exploration activities were inflationary, destabilising and inimical to growth, at least in the short-run. On another positive side, both companies showed increased technical efficiencies in the chosen time period. Petrobras enjoyed TE on average of 90% in the variables studied whereas Galp showed an average TE of 70%. These results reflect the corporate strategies of both firms, which focussed on achieving profitable and sustained growth and enhancing their efficiencies in their collective and individual activities. Keywords: Economic Growth; Exploration; Oil and Gas; Technical Efficiency; Strategic Alliance JEL Classifications: L1; L4; Q43